2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319321
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact dual pulse Doppler system based respiratory and heart rates estimation for CHF patients

Abstract: Long term continuous patient monitoring is required in many health systems for monitoring and analytical diagnosing purposes. Most of monitoring systems had shortcomings related to their functionality or patient comfortably. Non-contact continuous monitoring systems have been developed to address some of these shortcomings. One of such systems is non-contact physiological vital signs assessments for chronic heart failure (CHF) patients. This paper presents a novel automated estimation algorithm for the non-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Studies have reported some commendable achievements, such as error of less than 0.5 breath per minute for respiratory rate and one beat per minute for heart rate [26,27,61]. In addition, the achieved accuracy of Doppler radar in measuring physiological parameters, such as respiratory rate is 92% [39], heart rate is 88% [39,59,81] to 91% [40], and with the addition of harmonics interference, the average error can be reduced further to 3.2% [84]. However, conventional FFT may not always be able to reliably separate the rich sinusoidal components due to smearing and leakage problems, particularly from the limited data samples [74].…”
Section: Time-frequency Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have reported some commendable achievements, such as error of less than 0.5 breath per minute for respiratory rate and one beat per minute for heart rate [26,27,61]. In addition, the achieved accuracy of Doppler radar in measuring physiological parameters, such as respiratory rate is 92% [39], heart rate is 88% [39,59,81] to 91% [40], and with the addition of harmonics interference, the average error can be reduced further to 3.2% [84]. However, conventional FFT may not always be able to reliably separate the rich sinusoidal components due to smearing and leakage problems, particularly from the limited data samples [74].…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…Besides clutters, other issues such as DC offsets, phase-nulling contributions, motions artefacts and electromagnetic interferences are also posing as challenges to the signal processing of Doppler radar signals [13,57]. Another major challenge in sleep monitoring application is the noise associated with unpredictable body movements, body orientations, changes in sleeping posture, multi-subjects cancellation, undesired harmonics and intermodulation [14,15,39].…”
Section: Others Sources Of Noisementioning
confidence: 99%
See 2 more Smart Citations
“…The mother wavelet for WPD is Symlet wavelet with 4 th order filter. The reason for choosing the Symlet wavelet is for the performance and accuracy as detailed in the authors' previous work [5].…”
Section: A Wavelets Extraction Processmentioning
confidence: 99%